Embryos of common thresher shark Alopias vulpinus in southern Brazil, south Atlantic Ocean - Mancini, P. L.; Amorim, A. F. (Blackwell Publishing, 2006)
Eight embryonic thresher sharks Alopias vulpinus (53.9-124 cm total length) were collected from two females caught by commercial longline off southern Brazil in September and November 2004. Morphometric measurements are provided. (c) 2006 the Authors.
Keywords: Alopias vulpinus; Brazil; common thresher shark; embryo size; lamniformes; south Atlantic